IMPLEMENTATION OF DIFFERENTIATED LEARNING: STUDENT AND TEACHER PERSPECTIVES IN THE CONTEXT OF MATHEMATICS IN PRIMARY SCHOOLS - Rimayasi; Rosmitha Sari, Eka; Agusalim; Anisa Rizkayati; Qonita Aprilia (JURNAL PENDIDIKAN GLASSER, 2025)
Differentiated learning is an approach that aims to accommodate students' needs and learning styles in the learning process. In learning mathematics in primary schools, students often face challenges in understanding abstract concepts, so flexible and responsive teaching strategies are required. This study aims to explore the application of differentiated learning methods in mathematics at State 2 Wameo Primary School, Baubau City, and evaluate teachers' and students' perspectives on the effectiveness of this approach. The research used a qualitative method with a case study approach. Data collection techniques included in-depth interviews with teachers and students, observation of learning activities, and analysis of learning documents. Participants consisted of fourth and fifth grade students who have various learning styles, as well as teachers involved in the implementation of differentiated learning. The results show that differentiated learning helps students understand math materials better through media and tasks that suit their learning styles. However, teachers face challenges in providing equal attention, adjusting learning strategies and distributing tasks fairly due to limited time and resources. This research contributes to the development of more inclusive and adaptive mathematics learning strategies and provides a basis for educational policies that support students' diverse learning needs, but still provides a basis for educational policies that support students' learning needs.